Hearing loss and social support in urban and rural communities*. (3rd August 2018) - Hay-McCutcheon, Marcia J.; Hyams, Adriana; Yang, Xin; Parton, Jason
Abstract: Objective: Perceived social support and hearing handicap were assessed in adults with and without hearing loss who lived in different geographical regions of Alabama. Design: The Hearing Handicap Inventory for Adults (HHIA) assessed emotional and social consequences of hearing loss. The Medical Outcomes Study (MOS) Social Support Survey and the Social Functioning, Role Emotional and Mental Health scales of the SF-36 were administered. Study sample: Data were collected from 71 study participants with hearing loss and from 45 adults without hearing loss. Results: Degree of hearing loss and outcomes from the HHIA did not differ between adults who lived in rural or urban settings. Tangible support was poorer for adults with hearing loss who lived in rural settings compared to those who lived in urban settings. For adults without hearing loss, residency was not associated with tangible support. For these adults, income was associated with other types of social support (i.e. informational support, affection, positive social interaction). Conclusions: Adults with hearing loss living in rural areas had poor perceived tangible support. The provision of support to address a hearing loss could be worse for these adults compared to adults who lived in urban settings.